Acute exercise reduces feeding by activating IL-6/Tubby axis in the mouse hypothalamus - de Oliveira Micheletti, Thayana; Cassia dos Santos, Andressa; Rocha, Guilherme Zweig; Silva, Vagner Ramon Rodrigues; Quaresma, Paula Gabriele Fernandes; Assalin, Heloisa Balan; Junqueira, Felipe Silva; Ropelle, Eduardo Rochete; Oliveira, Alexandre Gabarra [UNESP]; Saad, Mario Jose Abdalla; Prada, Patricia de Oliveira (Frontiers, 2022)
Background: Acute exercise contributes to decreased feeding through leptin and interleukin/Janus kinase 2/signal transducers and activators of transcription 3 (IL-6/JAK2/STAT3) signaling. Considering the pleiotropic use of substrates by JAK2 and that JAK2 can phosphorylate the Tubby protein (TUB) in CHO-IR cells, we speculated that acute exercise can activate the IL-6/JAK2/TUB pathway to decrease food intake. Aims: We investigated whether acute exercise induced tyrosine phosphorylation and the association of TUB and JAK2 in the hypothalamus and if IL-6 is involved in this response, whether acute exercise increases the IL-6/TUB axis to regulate feeding, and if leptin has an additive effect over this mechanism. Methods: We applied a combination of genetic, pharmacological, and molecular approaches. Key findings: The in vivo experiments showed that acute exercise increased the tyrosine phosphorylation and association of JAK2/TUB in the hypothalamus, which reduced feeding. This response was dependent on IL-6. Leptin had no additive effect on this mechanism. Significance: The results of this study suggest a novel hypothalamic pathway by which IL-6 released by exercise regulates feeding and reinforces the beneficial effects of exercise.
Keywords: exercise; food intake; hypothalamus; IL-6; JAK2; Tubby mouse